STUDY OF ETIOLOGY OF TRAUMATIC URETHRAL STRICTURES IN MALE (Latakia University Journal -Medical Sciences Series, 2024)
* The Aim:Determining the causes of traumatic urethral strictures, especially by medical trauma* Patients and methods:The study consisted of (120) patients with traumatic urethral stenosisPatients were distributed into two groups: group A: external traumaGroup B: iatrogenic, who were distributed into five subgroups (catheterization, cystoscopy, hypospadias surgery, prostatectomy, tur ).* Results:The mean age was 46 years. Iatrogenic was the most common (76.6%), traumatic (23.33%). tur (40%) and catheterization (34%) are the most causing iatrogenic stricture.In the anterior strictures, the most common is Iatrogenic, while in the posterior strictures; the external trauma. The most causes of iatrogenic anterior strictures were tur , and the most common causes of posterior strictures were prostatectomy.Iatrogenic strictures occur mainly over 45 years old, while external traumatic strictures occur in younger than 45 years old. In patients over 45 years old, the most common iatrogenic causes were transurethral resection, while in patients less than 45 years old, urethral catheterization and hypospadias repair.*Conclusion:Iatrogenic are the most common causes of strictures, (tur) and catheterization. The etiology differs in age and depending on the stricture site.